2017
DOI: 10.1097/j.pain.0000000000000898
|View full text |Cite
|
Sign up to set email alerts
|

Hyperalgesic priming (type II) induced by repeated opioid exposure: maintenance mechanisms

Abstract: We previously developed a model of opioid-induced neuroplasticity in the peripheral terminal of the nociceptor that could contribute to opioid-induced hyperalgesia, type II hyperalgesic priming. Repeated administration of mu-opioid receptor (MOR) agonists, such as DAMGO, at the peripheral terminal of the nociceptor, induces long-lasting plasticity expressed, prototypically as opioid-induced hyperalgesia and prolongation of prostaglandin-E2-induced hyperalgesia. In this study, we evaluated the mechanisms involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 79 publications
6
73
2
Order By: Relevance
“…In contrast with our results, Araldi et al (2017; found that the SFK inhibitor SU-6656 did not inhibit CFA-induced latent sensitization at the relatively high dose of 27 nmol i.th.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our results, Araldi et al (2017; found that the SFK inhibitor SU-6656 did not inhibit CFA-induced latent sensitization at the relatively high dose of 27 nmol i.th.…”
Section: Discussioncontrasting
confidence: 99%
“…Nociceptive threshold testing. Mechanical nociceptive threshold was measured using an Ugo Basile Analgesymeter (Randall-Selitto pawwithdrawal device, Stoelting), which applies a linearly increasing mechanical force to the dorsum of a rat's hindpaw, with a dome-shaped plinth, as described previously Araldi et al, 2015Araldi et al, , 2017Ferrari and Levine, 2015). Rats were placed in cylindrical acrylic restrainers that provide ventilation, and allow extension of the hind legs from lateral ports to assess nociceptive threshold, while minimizing restraint stress.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that several inflammatory mediators, which act as agonists at cell surface receptors on nociceptor (Aley et al, 2000;Reichling and Levine, 2009;Bogen et al, 2012;Ferrari et al, 2013a,b) and MOR agonists (e.g., DAMGO, fentanyl, and morphine) (Araldi et al, 2015(Araldi et al, , 2017(Araldi et al, , 2018aFerrari et al, 2019), produce hyperalgesic priming, a form of nociceptor neuroplasticity thought to contribute to the transition from acute to chronic pain. A key feature of the primed nociceptor is that it responds to pronociceptive mediators, prototypically prostaglandin E 2 (PGE 2 ), with markedly enhanced and prolonged mechanical hyperalgesia (Aley et al, 2000;Parada et al, 2003bParada et al, , 2005Reichling and Levine, 2009;Ferrari et al, 2014Ferrari et al, , 2016Ferrari et al, , 2019Araldi et al, 2015Araldi et al, , 2017Araldi et al, , 2018aAraldi et al, ,c, 2019Khomula et al, 2017). Intradermal MOR agonists, in a dose that does not affect mechanical nociceptive threshold in opioid-naive rats, induces robust hyperalgesia in rats previously treated systemically with a MOR agonist (Araldi et al, 2018a).…”
Section: Inhibition Of Protein Translation Reverses Oihmentioning
confidence: 99%
See 1 more Smart Citation
“…This is defined as a prolonged latent hyper-responsiveness of nociceptors to inflammatory mediators subsequent to nerve damage (Aley et al, 2000; Kandasamy and Price, 2015; Reichling and Levine, 2009). The notion of hyperalgesic priming has also been applied as it relates to estrogen receptors (Ferrari et al, 2017b) and repeated opioid exposure (Araldi et al, 2017). We are unaware of evidence for similar processes in the CNS that may lead to covert processing of non-consciously perceived ‘stimuli’ that may lead to CNS hyperalgesic priming.…”
Section: The Tipping Point: Neurobiological Processes Brain Dysfumentioning
confidence: 99%